Peristaltic motion of Maxwell fluid subject to convective heat and mass conditions - Iqbal, Naveed; Yasmin, Humaira; Bibi, Aneela; Attiya, Adel A. (Ain Shams Engineering Journal, 2021)
This article concentrates on peristalsis of Maxwell fluid in a symmetric channel with heat and mass convective conditions. Analysis is given in presence of viscous dissipation. The relevant problems statements are constructed and solved for the series solutions of stream function, temperature and concentration. Regular perturbation technique is adopted for small wave number. Heat transfer coefficient is also derived. Results of temperature, concentration and heat transfer coefficient are graphically analyzed. Trapping phenomenon is studied. It is observed that heat and mass transfer Biot numbers have opposite effects on fluid temperature and concentration. Concentration distribution decays with the increase in Schmidt number and Soret number. Heat transfer coefficient has oscillatory behavior and magnitude of heat transfer coefficient increases when heat transfer Biot number enhances. In addition, similar trapping pattern is observed for relaxation parameter and wave number.